2022
DOI: 10.1021/jacs.1c11498
|View full text |Cite
|
Sign up to set email alerts
|

Photophosphatidylserine Guides Natural Killer Cell Photoimmunotherapy via Tim-3

Abstract: Natural killer (NK) cells, in addition to their cytotoxicity function, harbor prominent cytokine production capabilities and contribute to regulating autoimmune responses. T-cell immunoglobulin and mucin domain containing protein-3 (Tim-3) is one of the inhibitory receptors on NK cells and a promising immune checkpoint target. We recently found that phosphatidylserine (PS) binding to Tim-3 can suppress NK cell activation. Therefore, based on the therapeutic potential of Tim-3 in NK-cell-mediated diseases, we d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 59 publications
0
14
0
Order By: Relevance
“…Photoisomerization of multiple bonds, such as C=C and C=N double bonds, has been used in various fields. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] A photoinduced concerted bond rotation, where two or more adjacent bonds rotate simultaneously, is a rare phenomenon and is known to be essentially different from the well-studied photoinduced single chemical bond rotation because the reaction product, in which two or more bonds are isomerized from the starting material, can be directly afforded without the presence of intermediate isomers. 20,21 A simultaneous three-bond isomerization of a conjugated triene system 22 and Hula Twist (HT) of a hemithioindigo (HTI) motor 23,24 are only experimentally demonstrated photoinduced concerted rotations involving a C=C double bond.…”
Section: Introductionmentioning
confidence: 99%
“…Photoisomerization of multiple bonds, such as C=C and C=N double bonds, has been used in various fields. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] A photoinduced concerted bond rotation, where two or more adjacent bonds rotate simultaneously, is a rare phenomenon and is known to be essentially different from the well-studied photoinduced single chemical bond rotation because the reaction product, in which two or more bonds are isomerized from the starting material, can be directly afforded without the presence of intermediate isomers. 20,21 A simultaneous three-bond isomerization of a conjugated triene system 22 and Hula Twist (HT) of a hemithioindigo (HTI) motor 23,24 are only experimentally demonstrated photoinduced concerted rotations involving a C=C double bond.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Yang et al reported the first synthesis of a photoswitchable diacyl phosphatidylserine, named phoPS following a chemoenzymatic route, and they evaluated the activity of this lipid in autoimmune diseases . Using the Co-catalyzed epoxide opening described here, we also report a four-step route to similar derivatives dAzoPS and oleoyl-AzoPS (Scheme ).…”
mentioning
confidence: 99%
“…They designed a photoswitchable ligand, which could efficiently be induced or inhibited at varying wavelengths of light to fully understand the involvement of Tim-3 in the immune responses and its potential as a pharmacological checkpoint blockade target in pathologies that are triggered by NK cells. 6…”
mentioning
confidence: 99%
“…Yang et al synthesized an azobenzene moiety that is integrated within the tail end of PS which is a cis -olefin tail, further resulting in a photoswitchable tool called phoPS. 6 Precise spatiotemporal irradiation causes activation or inactivation of phoPS, facilitating optical regulation of NK cell initiation through Tim-3. After photomanipulation, analysis of binding kinetics revealed that cis -phoPS exhibits greater binding affinity to Tim-3 as compared to trans -phoPS.…”
mentioning
confidence: 99%
See 1 more Smart Citation